Non-invasive MRI Measurement of the Absolute CBV-CBF Relationship during Visual Stimulation in Healthy Humans - Ciris, Pelin Aksit (2013)
PURPOSE: The relationship between cerebral blood volume (CBV) and cerebral blood flow (CBF) underlies blood oxygenation level dependent functional MRI signal. This study investigates the potential for improved characterization of the CBV-CBF relationship in humans, and examines gender effects as well as spatial variations in the CBV-CBF relationship. METHODS: Healthy subjects were imaged non-invasively at rest and during visual stimulation, constituting the first MRI measurement of the absolute CBV-CBF relationship in humans with complete coverage of the functional areas of interest. RESULTS: CBV and CBF estimates were consistent with literature, and their relationship varied both spatially and with gender. In a region of interest (ROI) with stimulus induced activation in CBV and CBF at the P<0.05 significance level, a power function fit resulted in CBV = 2.1 CBF(0.32) across all subjects, CBV = 0.8 CBF(0.51) in females and CBV = 4.4 CBF(0.15) in males. Exponents decreased in both genders as ROIs were expanded to include less significantly activated regions. CONCLUSION: Consideration for potential gender related differences, as well as regional variations under a range of physiological states, may reconcile some of the variation across literature and advance our understanding of the underlying cerebrovascular physiology.